Pembuatan Karbon Aktif Dari Kulit Durian Sebagai Adsorbent Logam Fe - Febriansyah, Beni; Chairul, Chairul; Yenti, Silvia Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Durian peel is known as the waste that can pollute the environment. One effort to improve the economic value of the durian skin can be done with the process into activated carbon. This study aims to obtain optimum conditions for the use of activators of Kaliaum Hidroksida on the quality of activated carbon and activated carbon absorption of Fe metal. Activated carbon is made via two processes, namely the process of carbonization and activation at 320oC temperature with a solution of Kalium Hidroksida by varying the massa aktif carbon1, 1.5, 2, 2.5, dan 3 gr and adsorb time30, 60, 90, dan 120 menit. To determine the quality of activated carbon, activated carbon characteristics tested, such as moisture content, ash content, and the absorption of iodine. The results showed that the characteristics of activated charcoal SNI 06-3730-1995 meets the standards the water content of 14.12%, 5.46% ash content and absorption of I2 solution of 580.27 mg / g in adsorbing metals Fe. Application of Fe metal adsorption by activated carbon from durian skin with 3 grams of carbon mass variation and contact time of 90 minutes where the adsorption efficiency is 96.75%.Keywords: activated carbon, durian skin, potassium hydroxide